“Croatian Orthodox Church”: from Idea to Realisation - Prodić, Slobodan (Napredak, 2023)
The “Croatian Orthodox Church” was a religious institution whose founding was a completely political project of the Independent State of Croatia. After eliminating the Serbian Orthodox Church from the areas controlled by Ustasha regime and crimes committed against the civilians of Serbian origin and of Orthodox religion by that regime, under the huge pressure of Germany, Ante Pavelić accepted the already existing idea of forming the “Croatian Orthodox Church”. This religious organisation had the identical form as all other Orthodox churches. However, the main difference between this and other Orthodox churches was that this religious organisation was not recognised in any, primarily ecclesiastical-canonical way, by any other autocephalous churches. It was exactly because of this that the “Croatian Orthodox Church” represented a classic example of para-synagogue. As such, it is an interesting topic for researches, especially if we keep in mind current happenings on the geopolitical scene and modern attempts of founding new churches and destroying the unity and harmony among autocephalous Orthodox churches.